Characterization and mechanism of simultaneous degradation of aflatoxin B1 and zearalenone by an edible fungus of Agrocybe cylindracea GC-Ac2 - Guo, Changying; Fan, Lixia; Yang, Qingqing; Ning, Mingxiao; Zhang, Bingchun; Ren, Xianfeng (Frontiers in Microbiology, 2024)
Contamination with multiple mycotoxins is a major issue for global food safety and trade. This study focused on the degradation of aflatoxin B1 (AFB1) and zearalenone (ZEN) by 8 types of edible fungi belonging to 6 species, inclulding Agaricus bisporus, Agrocybe cylindracea, Cyclocybe cylindracea, Cyclocybe aegerita, Hypsizygus marmoreus and Lentinula edodes. Among these fungi, Agrocybe cylindracea strain GC-Ac2 was shown to be the most efficient in the degradation of AFB1 and ZEN.Under optimal degradation conditions (pH 6.0 and 37.4°C for 37.9 h), the degradation rate of both AFB1 and ZEN reached over 96%. Through the analysis of functional detoxification components, it was found that the removal of AFB1 and ZEN was primarily degraded by the culture supernatant of the fungus. The culture supernatant exhibited a maximum manganese peroxidase (MnP) activity of 2.37 U/mL. Interestingly, Agrocybe cylindracea strain GC-Ac2 also showed the capability to degrade other mycotoxins in laboratory-scale mushroom substrates, including 15A-deoxynivalenol, fumonisin B1, B2, B3, T-2 toxin, ochratoxin A, and sterigmatocystin. The mechanism of degradation of these mycotoxins was speculated to be catalyzed by a complex enzyme system, which include MnP and other 2 ligninolytic enzymes. It is worth noting that Agrocybe cylindracea can degrade multiple mycotoxins and produce MnP, which is a novel and significant discovery. These results suggest that this candidate strain and its enzyme system are expected to become valuable biomaterials for the simultaneous degradation of multiple mycotoxins.